Swimming behavior indicates stress and adaptations to exercise - Yu, Sen; Liu, Lantao; Li, Min; He, Siyan; Hu, Yang; Sun, Shichao; Yan, Yizhen; Zhao, Fangfang; Cheng, Xiangrong; Li, Jia; Gao, Feng; Liu, Yong; et al. (Frontiers in Physiology, 2024)
Behaviors of swimming rodents are not uniform, exhibiting large variations, which may underlie the individual differences in swimming exercise-induced benefits. The study aimed to monitor individualized swimming behavior and evaluate its biological significance. A swimming tank which can monitor individualized rodent swimming behavior during exercise was established. A total of 45 mice were subjected to swimming training for 1 month (1 h per day) and the swimming behaviors of each mouse were recorded. The swimming behaviors of mice displayed considerable variations in aspects of distance, velocity, and area preference. For example, nearly one third of mice preferred to swim in central area and most of the mice exhibited an even area distribution. Long-term exercise 2 training improved cardiac systolic function and decreased blood pressure in mice, but hardly changed swimming behaviors. Analyses of the relationship between swimming behavior and cardiovascular adaptations to exercise training revealed that swimming behavior indicated the biological effects of swimming training. Specifically, mice which preferred swimming at the central zone or were trainable in behavior during 1-month training exhibited better outcomes in cardiac function and blood pressure post long-term exercise. Mechanistically, a centralized swimming behavior indicated a smaller stress during exercise, as evidenced by a milder activation of hypothalamic-pituitary-adrenal axis. These results suggest that swimming behavior during training indicates individualized adaptations to long-term exercise, and highlight a biological significance of swimming behavior monitoring in animal studies.